Surgical implants. Specification for surgical bone screws of 4 mm, 3.5 mm and 3 mm nominal sizes, countersunk surfaces on bone plates, twist drills, taps and screwdrivers Part 5, (31st October 1983) - British Standards Institution,
No abstract available